2000
DOI: 10.1111/j.1532-849x.2000.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular implant overdenture treatment: Consensus and controversy

Abstract: A literature review of implant overdenture treatment for the edentulous mandible is presented. The report focuses on the knowledge base for this treatment modality, in an effort to distinguish between areas that are well characterized and enjoy a higher level of consensus among practitioners as compared with those that are more controversial and not clearly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 48 publications
(86 reference statements)
1
67
1
4
Order By: Relevance
“…Two solitary Titanium-aluminum-vanadium (Ti-6Al-4V) [23][24][25] implants [3] were embedded at a distance of 13 mm from the midline [26]. These were commercially available as Endopore implants (EndoPore TM ) [17,27,28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two solitary Titanium-aluminum-vanadium (Ti-6Al-4V) [23][24][25] implants [3] were embedded at a distance of 13 mm from the midline [26]. These were commercially available as Endopore implants (EndoPore TM ) [17,27,28].…”
Section: Methodsmentioning
confidence: 99%
“…Fewer implants with a removable prosthesis offer a less complex, less expensive and thus readily acceptable option for an edentulous patient. Consequently, Implant supported removable prosthesis has gained significant psychologic acceptance [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…3 Implants reduce further bone resorption and the long-term success rate of implants in the lower mandible is at least 95% 3 and there are few serious complications. 5 In 1998, 13% of adults overall and 58% of adults aged 75 and over in the UK were edentulous 9 . In the most recent US oral health survey (1999)(2000)(2001)(2002)(2003)(2004), 31.3% of adults aged over 75 and 23.9% of those aged 65-74 years were edentulous.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than 50% of those with mandibular complete dentures may have problems with stability and retention. 4,5 These factors cause a range of problems. Many patients experience pain when eating and chewing and are often concerned about the denture moving when eating, speaking or laughing and report fears about the negative effect of dentures on social situations.…”
Section: Introductionmentioning
confidence: 99%
“…Toutefois, il existe encore des controverses quant aux concepts et thérapeutiques à adopter, en particulier pour le nombre d'implants, leur mise en charge, le type de système d'ancrage à utiliser, et la maintenance à réaliser [13]. Il faut cependant souligner que le système d'ancrage retenu doit occuper un volume réduit afin de se situer dans le couloir prothétique et ne pas entraver le profil d'extrados de la prothèse.…”
Section: Discussionunclassified